A Study of the Problematic Status of Teaching Arabic in Iran: An attempt to Activate Teaching Arabic in Iran - Shamsabadi, Hossein (IAIN Samarinda, 2016)
Many have spoken of Arabic as the language of the Holy Quran and the medium of the Islamic civilization drawing on its status and importance, its role, and its peculiar characteristics.. The current study touches upon the problems and challenges inflicting Arabic in Iran. As such the main objective of the current study is to both maintain the importance of Arabic in Iran and to find solutions for such problems and challenges. Arabic can help the learners dramatically, as it is such a powerful means toward social development. The researcher has not only attempted to address the many problems and obstacles in the path of teaching Arabic in Iran, but to propose solutions focusing on a comparative methodology that would deal with the limitations imposed on both teachers and learners, the well/ill-receptions of this language and it learners in Iran, and such issues as lack of motivation among learners.